Functionalization of MOFs via a mixed-ligand strategy: enhanced CO2 uptake by pore surface modification. Issue 15 (26th March 2018) - Liu, Bo; Zhou, Hui-Fang; Hou, Lei; Wang, Yao-Yu
Abstract : Two isostructural MOFs based on rare quaternary SBUs with a new (3, 3, 4, 6)-connected topology have been assembled, which possess high porosity with highly polar pore systems, and also exhibit high uptake for CO2 and significant selectivity for CO2 over CH4 . Abstract : A new Zn(ii ) metal–organic framework (MOF) [Me2 NH2 ][Zn2 (BDPP)(HTZ)]·4DMF (1 ) (H4 BDPP = 3, 5-bis(3, 5-dicarboxylphenyl)pyridine, HTZ = 1 H -tetrazole) has been constructed under solvothermal conditions by using a mixed-ligand strategy. Structural analysis demonstrates that1 is a 3D framework based on four kinds of secondary building units (SBUs), which presents a rare structure constructed from quaternary SBUs and shows an uncommon (3, 3, 4, 6)-connected topology. In particular, 1 contains two shapes of 1D open channels with suitable pore sizes, high porosity, and a highly polar pore system decorated with uncoordinated N atoms and carboxylic O atoms, providing a good environment for selective adsorption of CO2 . Inspired by the structure of1 and reticular chemistry, 5-amino-1 H -tetrazole (ATZ) was used to replace 1 H -tetrazole to enhance CO2 sorption capacity by pore surface modification; as a result, an amino-functionalized MOF, [Me2 NH2 ][Zn2 (BDPP)(ATZ)]·4DMF (1-NH2 ) was successfully built.1-NH2 exhibits multipoint interactions between the CO2 molecules and the framework, resulting in better CO2 uptake and selectivity for CO2 over CH4 than1 .